EXPLORING HYPERGLYCEMIA-RELATED SEIZURES: A CASE SERIES - Chen, Hannah; Yee, Sim Sing; Lin, Chan Pei; Sieng, Florence Tan Hui (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Hyperglycemia-related seizures, though rare, represent a serious complication of uncontrolled diabetes, often occurring in the context of Hyperosmolar Hyperglycaemic State (HHS). We present a retrospective case series detailing the clinical characteristics, metabolic parameters and outcomes of patients admitted with hyperglycemia-related seizures. CASE Seven patients (4 females, 3 males) were included, with a median age of 64 years (range 16–76). All except one, a known defaulter, were on insulin therapy. Glycemic control was poor, with a median HbA1c of 9.9% (range 7.4–19.8). Random blood glucose levels at presentation ranged from 15 to 48.8 mmol/L. Serum sodium ranged from 120 to 150 mmol/L and serum osmolality ranged from 292.2 to 361.1 mOsm/kg. Three had HHS and one had overlapping diabetic ketoacidosis. Generalised tonic-clonic (GTC) seizures were the most common presentation (n = 6), while one had focal seizures. Only one patient had a prior history of stroke; none had known epilepsy. Three patients required intubation for airway protection. Potential confounders included dementia (n = 2), hypertensive crisis (n = 1), liver cirrhosis (n = 2, including one with history of substance abuse), and sepsis (n = 1). Brain CT most commonly showed cerebral atrophy with small vessel disease (n = 4); two had concurrent multifocal infarct. Two EEGs were performed, showing no epileptiform changes. Most patients achieved seizure control following normalization of blood glucose. Three patients were started on antiepileptic medications, and two of these patients were discharged on the same medications. The mortality rate was high, with three deaths occurring during the study period. One of these patients developed a total anterior circulation infarct. CONCLUSION Our findings suggest that GTC seizures are more prevalent in patients with severe hyperglycemia. The absence of epileptiform activity on EEG supports a metabolic etiology. Early recognition, aggressive glycemic management, and comprehensive post-discharge follow-up are important. These measures may improve neurological outcomes and reduce the high mortality associated with this complication.